Enterprise architecture framework selection for higher education using TOPSIS method - Komariah Hildayanti, Siti; Rahmanda Putra, Rian; Suhandi, Nazori; Sanmorino, Ahmad; Antony, Fery; Heryati, Agustina; Deviana, Hartati; Gustriansyah, Rendra (International Journal of Engineering and Technology, 2019)
In developing enterprise architecture (EA), it is necessary to adopt or select EA framework for enterprise architecture especially in the higher education. There are various frameworks that can be used for the development of enterprise architecture. There are several established EA frameworks in use today. Some of these frameworks were developed for very specific areas, while others have a wider function. This study aims to select the appropriate EA framework using TOPSIS method, applied to Higher Education. Seven eligible EA criteria are: grounded, cohesive, easy to customize, vendor free, technology independent, neutral-domain, and scalable will be processed by TOPSIS method. The calculation result with TOPSIS method shows that TOGAF is EA framework recommended to be implemented in higher education because it meets the criteria needed by EA framework.Â